Biochar differentially affects the cycling and partitioning of low molecular weight carbon in contrasting soils. (January 2015) - Farrell, Mark; Macdonald, Lynne M.; Baldock, Jeff A.
Abstract: Biochar application to soils has received much attention due to the potential for dual benefits of improved fertility and carbon (C) sequestration. Whilst its effect on C and nitrogen (N) cycling in soils has been investigated previously, this has usually either focussed on the bulk soil organic matter, or a single compound such as glucose. Five low molecular weight dissolved organic C (LMWDOC) substrates (three sugars, one amino acid, one organic acid) were selected for a 14 C-CLPP experiment from which turnover rate ( t 1/2 ) and immediate carbon use efficiency (CUE) of the substrate were estimated. We demonstrated that whilst soil type had the greatest effect on soil microbial function, the addition of biochar also influenced microbial turnover and CUE of the substrates, most notably in the lowest fertility soil. We also identified that the relationship between turnover and CUE of the five substrates differed substantially, and the effect of biochar and soil type was more pronounced in the amino acid than the organic acid. This effect tended to be greatest in biochars produced at 450 °C, and less pronounced with the addition of biochars produced at 550 °C, though these trends were not consistent for all compounds in all soils tested. We conclude biochars and soils interact to manifest non-systematic differences in turnover rates of LMWDOCs, and thus a variety of mechanisms are likely responsible for this observation. As these compounds are most commonly found in the rhizosphere and can contribute a significant portion of photosynthetically-fixed C, and plant roots have been observed to grow preferentially around biochar particles, it is apparent that biochar may significantly affect the flow of LMWDOC through the microbial community in soils. Graphical abstract: Highlights: Biochar and soil have an interactive effect on LMWDOC utilisation. Both turnover rate and CUE of LMWDOCs are influenced by biochar addition. High temperature biochars tend to slow microbial utilisation of LMWDOCs. Turnover rates are higher in soils to which low temperature biochars are added.